Quantitative in vitro to in vivo extrapolation for developmental toxicity potency of valproic acid analogues. Issue 16 (9th May 2022) - Chang, Xiaoqing; Palmer, Jessica; Lumen, Annie; Lee, Un Jung; Ceger, Patricia; Mansouri, Kamel; Sprankle, Catherine; Donley, Elizabeth; Bell, Shannon; Knudsen, Thomas B.; Wambaugh, John; Cook, Bethany; et al.
Abstract: Background: The developmental toxicity potential (dTP) concentration from the devTOX quick Predict (devTOX qP ) assay, a metabolomics‐based human induced pluripotent stem cell assay, predicts a chemical's developmental toxicity potency. Here, in vitro to in vivo extrapolation (IVIVE) approaches were applied to address whether the devTOX qP assay could quantitatively predict in vivo developmental toxicity lowest effect levels (LELs) for the prototypical teratogen valproic acid (VPA) and a group of structural analogues. Methods: VPA and a series of structural analogues were tested with the devTOX qP assay to determine dTP concentration and we estimated the equivalent administered doses (EADs) that would lead to plasma concentrations equivalent to the in vitro dTP concentrations. The EADs were compared to the LELs in rat developmental toxicity studies, human clinical doses, and EADs reported using other in vitro assays. To evaluate the impact of different pharmacokinetic (PK) models on IVIVE outcomes, we compared EADs predicted using various open‐source and commercially available PK and physiologically based PK (PBPK) models. To evaluate the effect of in vitro kinetics, an equilibrium distribution model was applied to translate dTP concentrations to free medium concentrations before subsequent IVIVE analyses. Results: The EAD estimates for the VPA analogues based on different PK/PBPK models were quantitatively similar to in vivo data from both rats and humans, where available, and the derived rank order of the chemicals was consistent with observed in vivo developmental toxicity. Different models were identified that provided accurate predictions for rat prenatal LELs and conservative estimates of human safe exposure. The impact of in vitro kinetics on EAD estimates is chemical‐dependent. EADs from this study were within range of predicted doses from other in vitro and model organism data. Conclusions: This study highlights the importance of pharmacokinetic considerations when using in vitro assays and demonstrates the utility of the devTOX qP human stem cell‐based platform to quantitatively assess a chemical's developmental toxicity potency.